Marxism, Gandhism, Stalinism - Shah, C.G. (Bombay, 1963)
The book embodies an aggregate of articles published by the author in various magazines and lectures delivered by him before Marxist groups on diverse problems - philosophical, sociological, political and economic in past over three de cades. They have been classified into four sections viz. (1) Theoretical, (2) On India, (3) On Gandhism and (4) On Stalinism. Since the problems dealt with were chosen arbitrarily and not in conformity with a single scheme, they do not constitute a single pattern or form an inter-connected unified theme. The themes discussed represent an effort of the author to apply the Marxist method to some crucial problems.
Keywords: Communism